Reading the Direction of United States Policy through President Donald Trump's Statements - Iskandarsyah Siregar (LingLit Journal Scientific Journal for Linguistics and Literature, 2024)
This study critically examines the trajectory of United States policy during the presidency of Donald J. Trump (2017–2021) by analyzing his public statements through the lens of critical discourse analysis (CDA). Unlike traditional studies that focus on institutional outputs such as legislation or executive orders, this research foregrounds presidential rhetoric as a key instrument for articulating and shaping national policy. Drawing from 50 selected speeches, interviews, and tweets, the analysis reveals consistent rhetorical patterns reflecting themes of nationalism, protectionism, securitization, and polarization. The study categorizes Trump's discourse into five policy domains: foreign policy, economic policy, immigration, national security, and crisis communication. Within each domain, the research identifies how language was strategically employed to frame threats, mobilize support, delegitimize opposition, and justify controversial policy moves. The findings underscore the centrality of language in governance, demonstrating how presidential discourse acts as both a symbolic and operational force in shaping public perception and political direction. This article contributes to interdisciplinary conversations in political communication, discourse studies, and policy analysis, while offering a model for understanding how populist rhetoric redefines leadership and democratic norms in the digital age.